2023
DOI: 10.3390/su16010188
|View full text |Cite
|
Sign up to set email alerts
|

Review: Modified Urea Fertilizers and Their Effects on Improving Nitrogen Use Efficiency (NUE)

Samar Swify,
Romas Mažeika,
Jonas Baltrusaitis
et al.

Abstract: Urea has served as the primary nitrogenous fertilizer globally since the early 1950s. It is widely recognized as the most concentrated nitrogen source, containing approximately 46% nitrogen. Presently, around 220 million t/year of urea compounds are manufactured globally to fit the requirements of the agricultural sector. However, a significant drawback of this is that approximately 30–35% of the urea used in soil can be lost to the environment because of its limited effectiveness. Enhancing the efficiency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Furthermore, Tejada et al [45] demonstrated that urease and dehydrogenase were less affected by MCPA in soil containing higher contents of OM due to enhanced herbicide sorption and, therefore, reduced exposure of microbes to this ecotoxic molecule. The positive effect on urease activity after the incorporation of MCPA could result from the organic nature of the soil employed in the study (15% OM), or possibly the adaptation of rhizospheric microbes to similar compounds, as the soil sample was collected from a pasture that receives regular applications of the herbicide 2,4-D [9]. However, the lower urease activity observed in the co-application of urea and MCPA could be related to the enhanced ecotoxicity of the herbicide on more sensitive microbial populations that are involved in N-cycling, as observed previously for other pesticides [41,45,46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Tejada et al [45] demonstrated that urease and dehydrogenase were less affected by MCPA in soil containing higher contents of OM due to enhanced herbicide sorption and, therefore, reduced exposure of microbes to this ecotoxic molecule. The positive effect on urease activity after the incorporation of MCPA could result from the organic nature of the soil employed in the study (15% OM), or possibly the adaptation of rhizospheric microbes to similar compounds, as the soil sample was collected from a pasture that receives regular applications of the herbicide 2,4-D [9]. However, the lower urease activity observed in the co-application of urea and MCPA could be related to the enhanced ecotoxicity of the herbicide on more sensitive microbial populations that are involved in N-cycling, as observed previously for other pesticides [41,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst our study did not evaluate the transformation of soil OM to associate urea mineralization and pH shifts with the sorption of MCPA residues, our findings concerning enzymatic activities, particularly urease, provide evidence on how microbial urea mineralization and soil acidification can increase MCPA adsorption and slow its dissipation in organic soils in the long term. In this context, a recent study linked the active participation of ammonia-oxidizing bacteria with significant reductions in the dissipation of 2,4-D (>28%) in the presence of urea, highlighting the contribution of soil microbes in the interaction between urea fertilizers and acidic herbicides in soils [9]. On the other hand, increasing the bioavailability of MCPA to degrading microorganisms resulting from urea mineralization appears to be desirable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, further research is required to understand the association between N fertiliser addition and phytoremediation, particularly with As. Although cost-effectiveness is reported as an advantage [139] of N fertiliser, significant negative environmental impacts result from its addition, including atmospheric pollution and leaching. It is expected that N pollution will increase by up to 156% by 2025 [140].…”
Section: Nitrogen Fertilisersmentioning
confidence: 99%
“…The granulation process is also instrumental in urea fertilizer production. Urea fertilizer stands out as the most widely utilized solid nitrogenous fertilizer globally due to its excellent water solubility [3,4]. Compared to other nitrogenous fertilizers, urea provides a higher quantity of nitrogen to plants and soil owing to its concentrated nitrogen content of 46%.…”
Section: Introductionmentioning
confidence: 99%